2020
DOI: 10.1093/ibd/izaa097
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Impact of Mediterranean Diet on IBD Patients

Abstract: Background & Aims Malnutrition with the accumulation of fat tissue and nonalcoholic fatty liver disease (NAFLD) are conditions associated with inflammatory bowel disease (IBD). Visceral fat and NAFLD-related liver dysfunction can both worsen intestinal inflammation. Because the Mediterranean diet (Md) has been shown to ameliorate both obesity and NAFLD, the aim of this study was to analyze the impact of Md on the nutritional state, liver steatosis, clinical disease activity, and quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 41 publications
(19 reference statements)
3
131
0
1
Order By: Relevance
“…There is a large body of evidence proving that Mediterranean dietary patterns regulate inflammation in chronic disease [ 33 , 34 , 35 ] and in individuals with IBD; there is some evidence that adherence to MD is associated with lower risk of developing IBD [ 36 , 37 ] and decreased inflammation [ 38 , 39 ]. The results of our study stimulate further interest in the relationships between dietary patterns, nutrition adequacy, and disease pathogenesis in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of evidence proving that Mediterranean dietary patterns regulate inflammation in chronic disease [ 33 , 34 , 35 ] and in individuals with IBD; there is some evidence that adherence to MD is associated with lower risk of developing IBD [ 36 , 37 ] and decreased inflammation [ 38 , 39 ]. The results of our study stimulate further interest in the relationships between dietary patterns, nutrition adequacy, and disease pathogenesis in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The first group was represented by the Inflammatory Bowel disease (IBD) patients ( n = 100; 54 men, 46 women; age 51.2 ± 1.41 year), recruited for the study at the clinic of the Gastroenterology Unit of the University Hospital Company (AOU) Monserrato (CA), Italy and included Crohn’s disease (CD) ( n = 44) and ulcerative colitis (UC) patients ( n = 56); the second group included healthy control (HC) subjects ( n = 99; 59 men, 40 women; age 47.3 ± 1.42 year) recruited by means of a public announcement at the local University, so as to have two populations matched for age ( χ2 = 4.33, p = 0.12) and gender ( χ2 = 0.64, p = 0.43). IBD diagnosis was obtained by a combination of clinical examination, endoscopy and radiology, and by means of the Crohn’s Disease Activity Index (CDAI) and Partial Mayo Score (PMS), the disease activity was evaluated for CD and UC patients, respectively [ 62 ]. All tested patients with CD and UC were recovering from the disease and were treated with cortisone or mesalamine or 5-ASA agents or monoclonal antibodies against TNF-α.…”
Section: Methodsmentioning
confidence: 99%
“…A prospective study aimed to identify the impact of Md on the nutritional state, liver steatosis, clinical disease. The study reported a significant reduction of malnutrition-related parameters and liver steatosis was observed in UC patients after short-term dietary intervention 48 . Specifically they noticed that after 6 months of a Mediterranean diet fewer patients with UC had active disease (14 of 59 [23.7%] at start of trial vs 4 of 59 [6.8%] at 6 months following diet, P = 0.004) and furthermore, this study highlighted that a meditteranean diet was associated with an increase in quality of life 48 .…”
Section: Mediterranean Dietmentioning
confidence: 87%